2022
DOI: 10.28991/cej-2022-08-12-012
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Recruitment, Selection, and Training Practices on Employee Performance in the Construction and Related Industries

Abstract: The human resource management of a company is important in today's competitive business environment because employees are the support of the company. The performance of employees is crucial to the success of any corporation. Therefore, this study aims to identify the factors that contribute to better employee performance (EP). In this study, recruitment, selection, and training strategies are examined for their influence on EP in the UAE public sector, including the construction and related industries. Researc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 26 publications
0
2
0
2
Order By: Relevance
“…It was found that one reason for the skilled shortage is due to the current workers not being satisfied with their current income level and poor working conditions are obstacles to attract high quality talents in the domestic and overseas market [19]. Therefore, it is essential for companies to develop effective recruitment and incentive policies to attract skilled talents to work in the industry, as suggested by Alduhoori et al [39]. The Government also need to develop right working visa policies to attract skilled workers from the overseas market.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was found that one reason for the skilled shortage is due to the current workers not being satisfied with their current income level and poor working conditions are obstacles to attract high quality talents in the domestic and overseas market [19]. Therefore, it is essential for companies to develop effective recruitment and incentive policies to attract skilled talents to work in the industry, as suggested by Alduhoori et al [39]. The Government also need to develop right working visa policies to attract skilled workers from the overseas market.…”
Section: Discussionmentioning
confidence: 99%
“…Alduhoori et al [39] found that there are direct positive relationships between recruitment process, selection, training and employee performance. Insufficient recruitment and incentive policies are also main barriers to recruitment staff in the construction industry in Australia.…”
Section: Hypotheses Developmentmentioning
confidence: 99%
“…Jurnal 1 : hasil menunjukan bahwa proses rekrutmen dan seleksi yang berhasil dapat meningkatkan kinerja karyawan. Lebih spesifik, hasil penelitian menunjukkan bahwa seleksi yang efektif memiliki pengaruh positif dan signifikan terhadap kinerja karyawan (Aldhuhoori et al, 2022). 2.…”
Section: Hasil Analisis Qa2 Pengaruh Rekrutmen Dan Seleksi Terhadap K...unclassified
“…Pentingnya praktik rekrutmen dan seleksi yang efektif dalam meningkatkan kinerja karyawan telah diakui oleh beberapa penelitian. Aldhuhoori et al (2022) dan Mira et al (2019b) menemukan bahwa praktik rekrutmen dan seleksi yang baik dapat meningkatkan kinerja karyawan, sementara praktik yang buruk dapat menurunkannya. Santos (2020) mengemukakan bahwa rekrutmen yang terprogram dengan baik saja tidak cukup, tetapi harus dikombinasikan dengan seleksi berkualitas tinggi untuk meningkatkan kinerja karyawan.…”
Section: Hasil Analisis Qa3 Bagaimana Praktik Rekrutmen Dan Seleksi D...unclassified